Treated Wastewater and Nitrate Transport Beneath Irrigated Fields near Dodge City, Kansas - Sophocleous, Marios; Townsend, Margaret A.; Vocasek, Fred; Ma, Liwang; KC, Ashok (Current Research in Earth Sciences, 2010)
Use of secondary-treated municipal wastewater for crop irrigation south of Dodge City, Kansas, where the soils are mainly of silty clay loam texture, has raised a concern that it has resulted in high nitrate-nitrogen concentrations (10-50 mg/kg) in the soil and deeper vadose zone, and also in the underlying deep (20-45 m) ground water. The goal of this field-monitoring project was to assess how and under what circumstances nitrogen (N) nutrients under cultivated corn that is irrigated with this treated wastewater can reach the deep ground water of the underlying High Plains aquifer, and what can realistically be done to minimize this problem. We collected 15.2-m-deep cores for physical and chemical properties characterization; installed neutron moisture-probe access tubes and suction lysimeters for periodic measurements; sampled area monitoring, irrigation, and domestic wells; performed dye-tracer experiments to examine soil preferential-flow processes through macropores; and obtained climatic, crop, irrigation, and N-application rate records. These data and additional information were used in the comprehensive Root Zone Water Quality Model (RZWQM2) to identify key parameters and processes that influence N losses in the study area. We demonstrated that nitrate-N transport processes result in significant accumulations of N in the thick vadose zone. We also showed that nitrate-N in the underlying ground water is increasing with time and that the source of the nitrate is from the wastewater applications. RZWQM2 simulations indicated that macropore flow is generated particularly during heavy rainfall events, but during our 2005-06 simulations the total macropore flow was only about 3% of precipitation for one of two investigated sites, whereas it was more than 13% for the other site. Our calibrated model for the two wastewater-irrigated study sites indicated that reducing current levels of corn N fertilization by half or more to the level of 170 kg/ha substantially increases N-use efficiency and achieves near-maximum crop yield. Combining such measures with a crop rotation that includes alfalfa should further reduce the amounts of residual N in the soil, as indicated in one of the study sites that had alfalfa in past crop rotations.